Sexual Harassment in International Law - Diah Mutiara Dewi (International Journal of Social Service and Research, 2023)
Sexual harassment within the realm of international law is a multifaceted and intricate matter, impacting numerous individuals worldwide annually. This article seeks to examine and assess the difficulties and potential advancements in safeguarding those affected by sexual violence on a global scale. By conducting a comprehensive examination of diverse international legal instruments, such as the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), the Convention on Human Rights, various regional agreements, and UN resolutions, the authors highlight the pivotal role that international organizations play in combatting sexual harassment. The article also underscores the legal enforcement challenges and the accountability of sexual harassment perpetrators at the international level. The lack of uniformity in the definition and punishment of sexual misconduct across different countries, along with restrictions on victims' access to the legal system, pose hindrances to effectively addressing this issue. Nonetheless, despite these obstacles, the article presents optimistic prospects concerning the advocacy efforts of civil society and the growing global awareness of the problem of sexual harassment. In transcending national borders, international initiatives aimed at addressing sexual harassment are gaining increasing significance to establish a safe and violence-free global environment.